Looking into EFL students’ perceptions in listening by using English movie videos on YouTube - Tengku Maya Silviyanti (Universitas Syiah Kuala, 2014)
This study investigated students’ interest in using YouTube movie videos in practicing their listening ability either inside or outside of class. This study used a mix of open and closed questionnaires adopted from Kelsen (2009) on the motivation of using YouTube for listening. 45 students enrolled in a Listening III class were taken as the sample. The findings showed that the highest motive for students to use it was because ‘using YouTube has been beneficial to their English, followed by ‘using YouTube is interesting’, then, ‘using YouTube motivated them to study English’ and ‘the YouTube material was relevant to what was studied in class”. The lowest motive included ‘using YouTube in class motivated them to use it to themselves to study English outside of classes. Furthermore, some students’ open responses to YouTube were: they can practice their English by watching native speakers; it has pictures so it is easy for students to understand the topic, and the materials were relevant since they were practicing listening. Yet, negative responses were also found such as they did not have internet connection at home, were not motivated to do it alone and were not assigned homework to use it. Thus, YouTube can be considered to be used as a material in listening class because it is found to provide many benefits for students.